Metacognitive strategy use effects on metacognitive awareness, self-efficacy, reading performance and motivation - Cequeña, Maria B. (2008)
This study on the impact of metacognitive strategies on freshman high school students' metacognitive awareness, self-efficacy, reading performance and reading motivation hopes to uplift students' self-efficacy as readers and to help them overcome their comprehension dificulties through metacognitive strategies. The study is a quasi-experiment and the respondents were composed of 4 heterogeneous classes with a total of 168 freshman students from two schools, public and private. They were given pretests and posttests of the ff instruments: CEM Standardized Reading Test, Self-efficacy Inventory (SEI), Metacognitive Awareness of Reading Strategies Inventory (MARSI), A Rhody Secondary Reading Attitude Assesment (RSRAA), and reasearcher-made Reading test. There was a significant relationship between reading performance and self-efficacy and between self-efficacy and metacognitive awareness.
Thesis (Ph.D. Reading Education)--University of the Philippines, Diliman.
Keywords: Reading (Secondary) -- Ability testing -- Philippines; English language -- Ability testing -- Philippines; Reading comprehension -- Ability testing -- Philippines; Metacognition -- Philippines